Catalogue of the Byzantine coins in the Dumbarton Oaks Collection and in the Whittemore Collection. Vol. II : Phocas to Theodosius III, 602-717. Pt. 2 : Heraclius Constantine to Theodosius III, 641-717. - Grierson, Philip. (Washington)
s. 385-728, s. xxiii-xlvi res.